AN ANALYSIS OF CHARACTERS AND CHARACTERIZATION IN WELLSâ€™ THE ISLAND OF Dr. MOREAU - Nadina Syahrina; Senny Alwasilah; Erik Rusmana; Iwan Dudy Gunawan (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This paper was entitled â€œAn Analysis of Characters and Characterization in Wells the Island of Dr. Moreauâ€. This paper discussed of the secondary characters and their characterizations on novel the island of Dr.Moreau which were Moreau itself and his experiments or beast folks. The background of this research was taken because the novel is science fiction. The characters might be representing of future. The depiction of characters and characterizations was the reason of this paper and the development. The object researches problems were the way of the author explained the characters and characterizations, the characters development, and how plotting line assisted the characters and characterizations were developed. The theories were used in this paper; narratology including characters and characterization, and literary works. The aims of this paper the comprehension on literary works and how to find out the signs. The methodology in this paper is used qualitative method and descriptive methodology to interpret the signs. The result of the object research problems the secondary characters were the flat characters. The character of Moreau was the antagonist on this novel, meanwhile the beast folks were tritagonist. The findings were taken by point of view, dialogue, and so on. For further research of this paper, it might be taken of semiotics to get deeper comprehension of characters on this novel.